PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA GURU PADA SD YANG TERLETAK DI WILAYAH TEGALTIRTO - Ratnasari, Diyan; Muttaqiyathun, Ani (Universitas Ahmad Dahlan, 2011)
The teacher is someone who has a job as a facilitator for students to learn and/or develop the basic potentials and capabilities through both secaraoptimal school educational institutions established by governments or private. Teacher performance is influenced by many factors and one of them is emotional intelligence. The task of teachers is to form graduates who are competent to use optimally their feelings in order to identify itself and its environment.Problems examined in this study were: (1) Is self-knowledge, self-control, motivation, empathy and social skills have a partial effect on the performance of teachers. (2) Is self-knowledge, self-control, motivation, empathy and social skills simultaneously affect the performance of teachers. The population in this study are teachers who teach in primary schools in the region Tegaltirto.The results showed that some self-knowledge, self-control, motivation, empathy no significant impact on teacher performance, whereas social skills affect teacher performance. The results showed that the variables simultaneously self-knowledge, self-control, motivation, empathy and social skills have a significant effect on the performance of teachers. Working together self-knowledge, self-control, motivation, empathy and social skills to contribute 31.8% of teacher performance. The result is expected to be useful to teachers and schools. The teachers are expected to continue to improve emotional, because with a good emotional skills will be able to improve its performance as a teacher.